Zen and the Unspeakable God : Comparative Interpretations of Mystical Experience - Blum, Jason N., 1977- (Book collections on Project MUSE., 2015)
"An interpretive approach to the study of mystical experience. Compares the experiences of Meister Eckhart, Ibn Arabi, and Hui-neng to reveal commonalities that have provocative implications for our understanding of consciousness"--Provided by publisher